(untitled) (Journal of Universal Science Research, 2025)
This thesis explores the peculiarities of idiomatic expressions in English and Uzbek languages with a focus on their usage in mass media. It analyzes the theoretical background of idioms, their applications in mass media, and provides a comparative analysis of idiomatic expressions in English and Uzbek newspapers.